ANALYSIS OF COASTLINE CHANGES IN RUPAT ISLAND USING REMOTE SENSING DATA AND GEOGRAPHIC INFORMATION SYSTEMS - Devi Puspita; Mubarak Mubarak; Nursyirwani Nursyirwani (Asian Journal of Aquatic Sciences, 2021)
This study was conducted from July to August 2021 in coastal areas of Rupat Island, Riau Province. Coastal zone is an unstable area toward change, because it is a rendezvous place for land and sea, which the line is called shoreline. The purpose of this study was to determine the distance of shoreline change and to find out the landcover change in the coastal area. Method used in this study is a shoreline overlay from Landsat 5 in 1988, 1996, 2004 and Landsat 8 OLI in 2012 and 2020 and classifiation of land cover using supervised classification and Rupat Island monogram. This research showed shoreline changes between 1988 and 2020, abrasion of 106,55 hectares and accretion of 58,28 hectares. The largest land cover change was the decrease of dryland agriculture and forest area of 1530.80 hectares and 726.92 hectares. The largest addition of area occurred on the plantation that is equal to 741.02 hectares